Gender and Society Course at City College of Calamba: Classroom Learning and Advocacy Engagement - Mary Rose F. Montano; Anna Rhea C. Opeña; Jeanne Mae L. Ilao; Julie Ann Azucena-Orajay; Marilyn R. Garma; Kathleen R. Reyes (People and Behavior Analysis, 2026)
Education plays a critical role in shaping students’ engagement in gender advocacy; however, existing studies on gender-responsive pedagogy largely focus on attitudinal outcomes, with limited empirical evidence on how classroom learning translates into actual advocacy engagement within specific course contexts. Addressing this gap, this study examines how classroom learning in a Gender and Society course influences students’ advocacy engagement, particularly regarding attitudes, motivation, perceived barriers, and real-life application in a localized higher education setting. Using a descriptive–correlational quantitative design, data were collected from 164 students through a validated Likert-scale survey. Descriptive statistics and Pearson’s r were employed to analyze relationships among classroom learning, motivation, barriers, and advocacy engagement. Findings indicate that the course significantly enhanced students’ advocacy-related attitudes and motivation (M = 4.68; SD = 0.54). Teaching methods demonstrated a strong positive relationship with motivation (r = 0.640) and a moderate relationship with real-life advocacy application (r = 0.522). While perceived barriers such as limited opportunities and lack of knowledge were identified (M = 3.10), they did not significantly influence motivation (r = 0.062), suggesting that supportive and participatory pedagogical practices can outweigh perceived constraints. Overall, the findings confirm that classroom learning extends beyond awareness and contributes to students' actual advocacy behavior. This study provides empirical evidence linking gender pedagogy to advocacy engagement within a specific course and institutional context. It emphasizes the necessity of integrating experiential and advocacy-based strategies in gender education to sustain student engagement beyond the classroom.